2019
DOI: 10.1016/j.pt.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex Sorting for Pest Control: It’s Raining Men!

Abstract: In the pursuit of better pest-and vector-control strategies, attention returns to an old proven technology, the sterile insect technique (SIT) and related insect population-suppression methods. A major obstacle for any of these approaches that involves the release of sterile males is the separation of males from females during the mass rearing stage, in order to improve the cost-efficiency of these methods and to prevent the release of biting and disease-vectoring females. This review describes recent sex-sort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 96 publications
0
66
0
Order By: Relevance
“…Traditionally the construction of genetic sexing lines was based on linking a selectable marker gene, such as insecticide resistance 12,18,19 , the temperature-sensitive lethal (TSL), and phenotypic loci 25 to a Yautosome or X-autosome via induced chromosomal translocations. Such engineered lines are not stable, and chromosomal rearrangements will break the genetic linkage between a selective marker and a sex chromosome 13,15,18,25,31,32 . It was found that when large numbers of insects were produced from an engineered GSS line, rare chromosomal rearrangements persisted or were selected for, and would contaminate the original line making it unusable for sex sorting 15,32 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Traditionally the construction of genetic sexing lines was based on linking a selectable marker gene, such as insecticide resistance 12,18,19 , the temperature-sensitive lethal (TSL), and phenotypic loci 25 to a Yautosome or X-autosome via induced chromosomal translocations. Such engineered lines are not stable, and chromosomal rearrangements will break the genetic linkage between a selective marker and a sex chromosome 13,15,18,25,31,32 . It was found that when large numbers of insects were produced from an engineered GSS line, rare chromosomal rearrangements persisted or were selected for, and would contaminate the original line making it unusable for sex sorting 15,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Such engineered lines are not stable, and chromosomal rearrangements will break the genetic linkage between a selective marker and a sex chromosome 13,15,18,25,31,32 . It was found that when large numbers of insects were produced from an engineered GSS line, rare chromosomal rearrangements persisted or were selected for, and would contaminate the original line making it unusable for sex sorting 15,32 . The novel approach does not require the genetic linkage to sex chromosomes, instead it relies on the sex-specific rescue of lethality and any mutations affecting the functionality of antibiotic resistance genes will be selected out during sex-sorting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the release of sterile females could still result in crop damage due to oviposition or, in case of vector insects, in disease transmission. Sexing, classified as the removal of females from a mass-reared insect population, can be achieved by physical sorting, female-specific lethality, or by converting females into males 7 . Such solutions have been developed for multiple pest species using naturally occurring or classically induced mutations 8 11 or transgenesis 12 17 .…”
Section: Introductionmentioning
confidence: 99%